Permeability and selectivity study of polyethersulfone membrane for gas separation - Norshahira, Mohd Nor (2010)
The objective of this study is to develop and study the effect of polymer concentration and coating treatment on the membrane performance. The asymmetric polyethersulfone membranes were prepared through a dry/wet phase inversion process. The casting solution developed in this research consisted of polyethersulfone pellet, 1-methyl-2-pyrolidone (NMP) and methanol. There are three different membrane composition was prepared. The composition is 18 wt%, 23 wt% and 28 wt% of PES was used for permeability test PES membrane was divided into two categories: uncoated and coated with bromine solution. Casting process was done by using manual casting knife. Permeation test was carried out by testing CO2 and CH4 2permeating through the membrane to check the permeability and selectivity of respective gas to CH4 Different coating agent gave different rate of permeate while higher polymer concentration enhance the permeation rate. The PES membrane uncoated showed the higher selectivity compare to coat with bromine solution. The selectivity of CO2/CH4 was approximately 2.06 at 23% of PES concentration uncoated with bromine. It was believed that different concentration strongly affects the membrane performance.